FORECASTING MORTALITY FOR KAZAKHSTAN AND ASSESSING IT’S IMPACT ON THE STATE PENSION SPENDING - Sapin, A.M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This paper uses the mortality projection methods of Knykova A. and Sapin A., based on the original Lee-Carter model, in order to investigate mortality rates for Kazakhstan for the time period from 2018 to 2025 and assess their impact on the state pension spending in Kazakhstan. The results show that improvements in mortality rates have been increasing the number of years that people spend in retirement in Kazakhstan, which directly affects the public pension spending. The overall state pension spending is expected to increase in Kazakhstan from 2019 to 2025, reflecting the gradually increasing effect of mortality improvements, but the state pension spending’s share of GDP is projected to decline from 2021 to 2024. However, extra expenditures of the government on pensions due to future mortality improvements will increase gradually as a share of GDP over time and reach 0,02% in 2024